Climate Change: suggestions for the social science research agenda in Mozambique (Simbiótica. Revista Eletrônica, 2024)
The article proposes to analyse the situation of the theme of climate change as an object of study of the social sciences in Mozambique, followed by a proposal for a research agenda, considering that this country is one of the most vulnerable in the world to climate catastrophes. The work was prepared from a bibliometric review on the Scopus platform and through the search for relevant information on the subject in the official pages of the ten main universities in Mozambique. We argue that climate change has been marginalized as an object of study in the social sciences, which contrasts with the visibility of the issue in government institutions and intergovernmental panels. Finally, we propose environmental constructionism and decolonial ecology as tools that can mutually illuminate each other in the construction of a research agenda for the social sciences in Mozambique, providing a broad theoretical basis for addressing critical issues related to climate change and coloniality.
Keywords: climate change; denaturalization; social sciences; Mozambique